PELATIHAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA PADA UMKM: UPAYA DALAM MENGHINDARI KERUGIAN PADA PENGELOLAAN USAHA - Ani Setyowati; Scorina Dwiantari; Rusdiana Permanasari (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Financial statements are tools that present entity information in terms of assets, liabilities, and equity. With the financial statements, the financial condition of a business can be reflected. Financial reports can be used as a tool to evaluate as well as a tool in determining the capabilities of business actors in carrying out the operations of a business. Not only that, with the existence of financial reports, projections of future business operations can be better planned. However, for Micro, Small and Medium Enterprises or MSMEs, not all business actors are able and understand the importance of financial reports for the sustainability of these Micro, Small and Medium Enterprises or MSMEs. In reality, there are still many MSMEs who do not understand the importance of financial reports for the sustainability of a business or business. The results of this activity provide assistance and training for MSMEs to compile a financial report in a simple form in accordance with SAK EMKM which is regulated by the IAI Council.